The evolution of private returns to education during post-conflict transformation: Evidence from Mozambique - Sam Jones; Thomas Pave Sohnesen; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper estimates how private returns to education have evolved in the context of postconflict transformation in Mozambique. This has been characterized by rapid economic growth, significant expansion of the schooling system, but also limited structural change in a labour market dominated by small-scale agricultural activity. We find clear evidence that rates of return to education in the country have shifted over time - declining at lower levels of schooling, but remaining stable and possibly rising at the highest levels. This is consistent with increasingly convex returns, which are most evident among those in non-agricultural (wage) jobs. As such, workers today must accumulate more years of schooling to achieve the same expected return as in the past.
Keywords: I2; J31; O15; C23; 330; returns to education; workforce; pseudo-panel; Mozambique